О ПРИНЦИПЕ ИСТОРИЗМА И ИСТОРИЧЕСКОМ ПОДХОДЕ В БИБЛИОТЕЧНЫХ ИССЛЕДОВАНИЯХ (Библиосфера, 2010)
An analysis of methodological problems connected with the use of the principle of historicism and the historic approach to library research is given